Complete genome sequence of Conexibacter woesei type strain (ID131577T). Issue 2 (March 2010) - Pukall, Rüdiger; Lapidus, Alla; Glavina Del Rio, Tijana; Copeland, Alex; Tice, Hope; Cheng, Jan-Fang; Lucas, Susan; Chen, Feng; Nolan, Matt; Bruce, David; Goodwin, Lynne; Pitluck, Sam; et al.
Abstract The genusConexibacter (Monciardiniet al. 2003) represents the type genus of the familyConexibacteraceae (Stackebrandt 2005, emend. Zhiet al. 2009) withConexibacter woesei as the type species of the genus.C. woesei is a representative of a deep evolutionary line of descent within the classActinobacteria . Strain ID131577T was originally isolated from temperate forest soil in Gerenzano (Italy). Cells are small, short rods that are motile by peritrichous flagella. They may form aggregates after a longer period of growth and, then as a typical characteristic, an undulate structure is formed by self-aggregation of flagella with entangled bacterial cells. Here we describe the features of the organism, together with the complete sequence and annotation. The 6, 359, 369 bp long genome ofC. woesei contains 5, 950 protein-coding and 48 RNA genes and is part of theG enomic E ncyclopedia of B acteria and A rchaea project.